Centreline formation of the Nb(C,N) eutectic in 0.15% C; 0.0071% N; 0.022% Nb; 0.033% Al and 0.003% S structural steel - Bernetič, Jure (Materiali in tehnologije, 2008)
During a routine control, a very small through thickness reduction of area was found for one tensile specimen of a 90-mm plate. Careful investigations of the fracture and the section of specimens cut from the as-solidified continuously cast 250-mm slab showed that the cause was the presence of coarse particles of niobium carbo-nitride as a constituent of the quasi-eutectic Fe-Nb(C,N) that forms because of the centerline segregation of niobium.
Keywords: konstrukcijska jekla; plošče; kontrakcije; evtektiki; niobijev karbonitrid